Efficacy and safety of trabeculectomy with mitomycin C for childhood glaucoma: a study of results with long-term follow-up (Clinics, 2008)
OBJECTIVE: To evaluate the safety and effectiveness of trabeculectomy with mitomycin C in the management of childhood glaucoma. INTRODUCTION: The use of antifibrotic agents enhances the success of trabeculectomy performed in both adults and children. METHODS: A retrospective chart review (1991-2001) of 114 patients (114 eyes) from 0-14 years of age with congenital or developmental glaucoma. These patients underwent trabeculectomy with mitomycin but had not been previously treated with any antifibrotic agent. RESULTS: The mean patient age was 57.36 51.14 months (range: 0.5-168 months). Treatment was considered successful in 63 eyes (55.26%), with a mean intraocular pressure of 12.11 3.98 mmHg. For patients categorized as successfully treated, the mean follow-up time was 61.16 26.13 months (range 12-113 months). A post-surgical intraocular pressure of < 16 was observed in 47 eyes. The life-table success rates for intraocular pressure control at 24, 36, 48, and 60 months were 90.2%, 78.7%, 60.7% and 50.8%, respectively. The cumulative probability of failure was 40.8% at 12 months. Following surgery, endophthalmitis appeared in eight eyes (4.88%) after an average 36.96 months (range: 1.7-106 months). Other complications included expulsive hemorrhage, flat anterior chamber and bleb leak. DISCUSSION: It has been reported in pediatric patients that trabeculectomy without adjunctive antimetabolites achieves a successful outcome in 30% to 50% of cases. In our study, treatment was considered successful in 63 eyes (55.26%) within 61.16 26.13 months of follow-up. CONCLUSIONS: Trabeculectomy with mitomycin is safe and effective for short-term or long-term treatment of congenital or developmental glaucoma. The frequency of bleb-related endophthalmitis was no higher in these patients than that described in adults.